(untitled) (Research, Society and Development, 2020)
This study aims to verify in the scientific literature the particularities of Alzheimer’s Disease, the impacts on family members and caregivers, relating to the activities of the Integrated Multidisciplinary Assistance to Caregivers of People with Alzheimer’s Disease (AMICA) project at the Franciscana University. The data collection was the search for content present in previously published materials, such as national scientific articles, journals, theses and dissertations, coming from open access databases, such as CAPES Journals, Scielo, Disciplinarum Scientia and Virtual Libraries. Also, through participant observations, technical visits were made at AMICA and through this, reports of experiences described during this work. Consequently, an intervention planning was made, and then, the action, with a view to the dissemination of the project in other areas outside the university. The results indicate knowledge about the pathology, its definition, cause, symptoms and limitations, as well as the importance of looking at caregivers and the functioning in the group mentioned. We conclude by emphasizing that the theme is ideal for informing those involved and interested, reinforcing the value of the existence of a support group along the lines of AMICA.